KEGAGALAN DALAM BERDAKWAH (Kajian Teoritis Dalam Buku Penyebab Gagalnya Dakwah Karya Dr. Sayyid M. Nuh) - Ega Wigianti (An-Nida : Jurnal Komunikasi Islam, 2019)
This study aims to find out the causes of the failure of preaching described in the book "Penyebab Gagalnya Dakwah" by Dr. Sayyid M. Nuh. The book contains da'wah failures caused by the characteristics and actions taken by the dai. Some characteristics and behavior of dai that can cause failure of da'wah are futur, israaf, uzlah atau tafarrud, ittibaa’ul-hawa, ‘adamut-Tatsabbut aw at-tabayyun, faudhal waqti, dan al-mira wa-jadal. Without realizing it by Dai, these traits can cause the failure of da'wah. The researcher used the content analysis method or content analyst to analyze the contents of the data with a qualitative approach. The results of this study are to find out what factors can cause failure to preach, especially those presented in the book ‘Penyebab Gagalnya Dakwah’.